Nonparametric and semi-parametric evidence on the long-run effects of inflation on growth - Andrea Vaona; Stefano Schiavo (Kiel Institute for the World Economy (IfW), 2006)
In this paper we adopt both a nonparametric and a semi-parametric IV estimator to show that the relationship between inflation and output growth is non-linear and that there exists a threshold level below which inflation has no effects on growth.
Keywords: C14; E31; O49; 330; Growth; Inflation; Inflation; Wirtschaftswachstum; Nichtparametrisches Verfahren; Schätzung; Welt